County Incarceration Rate and Stroke Death: A Cross‐Sectional Study of the Influence of Physical Environment, Health Care Access, and Community Mental Distress - Anders Larrabee Sonderlund; Emily A. Wang; Natasha J. Williams; Carol R. Horowitz; Antoinette Schoenthaler; Louisa W. Holaday (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Few studies assess the association between county‐level incarceration rates and stroke death, and none test mechanisms. We examine the link between county imprisonment rates and stroke death, testing pathways and identifying racial disparities. Methods In a cross‐sectional design, we regressed stroke death onto imprisonment rates, adjusting for poverty, racial composition, education, unemployment, insurance, and violent crime. Using bootstrap methodology, we tested mediation through sports/recreational facilities and food environment, mental health provider and primary care physician (PCP) access, and community mental distress. Data spanned 4 years (2016–2019) and included 2260 counties. Results Adjusted models indicated a 0.08 (95% CI, 0.05–0.10) increase in stroke deaths for every 1‐unit change in imprisonment rate. This association was mediated by food environment (indirect effect, 0.006 [95% CI, 0.000–0.014]), primary care physician access (indirect effect, 0.002 [95% CI, 0.000–0.006]), and mental distress (indirect effect, 0.014 [95% CI, 0.007–0.022]). Counties in the top versus bottom quintile of imprisonment rates had 86.26% larger Black populations and 23.46% smaller White populations. Counties in the top versus bottom quintile of stroke death had 88.94% larger Black populations and 16.19% smaller White populations. Conclusions Our results complement evidence that living in high‐jail‐incarceration counties contributes to stroke death and associated racial disparities. We provide new evidence on prison incarceration rates and the pathways underpinning this association. County‐level imprisonment rates and the identified mechanisms represent avenues for further research into how stroke death and disparities may be mitigated.